2021
DOI: 10.3390/ijerph181910016
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Rehabilitation Program in Idiopathic Pulmonary Fibrosis—A Single-Center Randomized Trial

Abstract: We investigated the usefulness and effectiveness of tele-rehabilitation on exercise capacity in patients with idiopathic pulmonary fibrosis (IPF). A randomized study was carried out, including stable patients with IPF for 3 months of tele-rehabilitation: video and chat consultations with a physiotherapist and workout sessions with a virtual physiotherapist agent (VAPA). Moreover, 6-minute walk test distance (6MWTD), forced vital capacity (FVC), diffusion capacity for carbon monoxide (DLCO), 7 days pedometry, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 27 publications
4
65
0
3
Order By: Relevance
“… The multifaceted VAPA platform and its digital environment (from Cerdan et al [ 27 ]) ( Figure 1 is taken from the paper “Tele-Rehabilitation Program in Idiopathic Pulmonary Fibrosis—A Single-Center Randomized Trial by Cerdan-de-las-heras et al [ 27 ], used under CC BY [ 28 ]/content modified from original). …”
Section: Figurementioning
confidence: 99%
“… The multifaceted VAPA platform and its digital environment (from Cerdan et al [ 27 ]) ( Figure 1 is taken from the paper “Tele-Rehabilitation Program in Idiopathic Pulmonary Fibrosis—A Single-Center Randomized Trial by Cerdan-de-las-heras et al [ 27 ], used under CC BY [ 28 ]/content modified from original). …”
Section: Figurementioning
confidence: 99%
“…The main characteristics of these eleven trials [14][15][16][17][18][19][20][21][22][23][24][25] are presented in Table 1a. These were published between 2008 and 2021 in seven countries, namely, the United States of America, China, Germany, Israel, Denmark, Japan, and Poland, with five studies performed in middle-high income countries and six in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of pulmonary rehabilitation ranged from 3 weeks to 6 months, and six studies 15,16,18,19,23,24 reported the follow-up time points from 3 to 6 months. Eight studies [14][15][16]18,[20][21][22]24 were in an outpatient setting and all studies were completed under the supervision of the researchers. The severity of idiopathic pulmonary fibrosis ranged from mild to moderate in most studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized trial of 3 months of tele-PR among 29 individuals with IPF with remotely delivered physical therapy sessions demonstrated better maintenance of the 6MWD over 6 months in the tele-PR group compared to the control group. No significant difference was found between groups for pedometer-measured steps per day [ 104 ]. Adherence to the intervention was 64% over the first 3 months; no adverse events were recorded.…”
Section: Limitations Of Evidence Regarding Telehealth Interventions T...mentioning
confidence: 99%